GDC-UTP System Studies - Muhamad Hafiz Bin Yaziz, Muhamad Hafiz (Universiti Teknologi Petronas, 2011)
The power system analysis studies serve as the basis for ensuring reliability, improving system performance and power quality, reducing operating costs, and providing a reliable supply power during system operation. Thus, this paper presents a case study for designing power supply system for a plant which will include load flow study, short circuit study and protection relay study. The studies mentioned will be conducted through simulation by using DIG SILENT Power Factory Software. This study will focus in island system which is Gas District Cooling (GDC) in Universiti Teknologi PETRONAS (UTP). The load flow study will be emphasized on loading and voltage. The short circuit study will be emphasized on fault current for three phase, line to line, line to ground and line to line to ground. Finally, the protections relay study is to know the correct Time Multiplier Setting (TMS) to make the relay operate coordinately. The purpose of this study to understand the importance of system study analysis in plant, study and performed the analysis simulation for designing a power system and finally to familiarize with software which is DIGSilent Power Factory. The system study should be done in Universiti Teknologi PETRONAS because of total blackout and increasing in load every year. The method that used to do this study such as gathering data, model the system in software and analysis the data. The simulation base on four scenarios for load flow study and short circuit study and one scenario for protection relay study. The result that obtained from this study is for load flow study, the voltage deviation with the limit base on PETRONAS Technical Standard (PTS). For short circuit study, the current faults that obtained from the study will not damage the buses. For protection relay study, some breaker has been suggested to have new Time Multiplier Setting (TMS) during overcurrent and cannot manage to do the earthfault due to limitation on software.